GROUND WATER LEVEL AND SOIL TEMPERATURE VARIATION ON TROPICAL PEATLAND IN EL NIÑO YEAR - Nur Wakhid; Siti Nurzakiah; Nurita Nurita; Zainudin Zainudin (Agric, 2018)
Water level (TMA) and soil temperature are two keys of environmental factors for ecosystem peatland study and for peatland ecosystem sustainability as well as crop productivity on peatland. On the other hand, climate change is another factor that cannot be avoided and affects the peatland ecosystem. Fluctuation of water level and soil temperature more severe on El Niño or dry years. Therefore, monitoring of water level and soil temperature on peatland ecosystem is important for sustainable peat management, especially on the dry years. The study objective was to determine the dynamics of water level and soil temperature on peatlands ecosystem in El Niño years and compare them to the normal year conditions. Water level and soil temperature were conducted automatically on rubber plantations on tropical peatland in Jabiren, Pulang Pisau, Central Kalimantan, from January to December 2015. Water level on the field and canal drainage on tropical peatlands followed the variations of precipitation. Although the average of annual precipitation on El Niño year is almost the same as normal year, but the water level and soil temperature show quite significant differences to the normal years. In addition, even water level was deeper and soil temperature is quite high in the dry season of El Niño years, but this field did not burn because productive plants were growth managed well by the owner.